ANALISIS PROSES OPERASIONAL PADA UMKM BARBERSHOP DI KABUPATEN BONE UNTUK MENENTUKAN KELAYAKAN USAHA (Studi kasus pada Bang Feed Barbershop) - Nurfadillah, Ika; Eliana, Eliana; Ramadhani, Sri; Yunita, Vira; Hasni, Hasni (Yayasan Nuraini Ibrahim Mandiri, 2025)
Bang Feed Barbershop is one of the MSMEs in Bone Regency that shows significant growth in the men's grooming service industry. This study aims to analyze the operational processes and assess the feasibility of the business from technical and managerial aspects. The approach used is descriptive qualitative through interviews and direct observations of the owners and employees. The results of the study show that Bang Feed Barbershop has a structured, flexible operational system, supported by adequate facilities and infrastructure. A fair and transparent profit-sharing system also enhances employee motivation. Additionally, the strategy of selecting the right location and expansion plans demonstrate a strong long-term business vision. Based on these findings, the business is deemed feasible to continue developing, while still paying attention to service quality and operational